Facial Gunshot Wounds - Volk, Angela S.; Shokri, Tom; Sokoya, Mofiyinfolu; Ducic, Yadranko; Hollier, Larry H., Jr. (Facial Plastic Surgery, 2019)
Craniomaxillofacial gunshot injuries, resulting from assault, suicide attempts, and accidental trauma, represent a major public health dilemma in the United States. Due to the extent of injury and resulting osseous and soft tissue loss, facial gunshot wounds pose a unique challenge to the reconstructive surgeon. Initial management should use advanced trauma life support principles with the goal of patient stabilization. Acute operative management should center around wound decontamination, debridement, and temporary closure. Historically, definitive surgical management focused on delayed reconstruction secondary to high rates of wound infections, necrosis, and ischemia. With improvements in imaging modalities, the advent of virtual surgical planning, and the popularization of microvascular free flaps, contemporary methods have shifted toward earlier more definitive reconstruction. Autologous free tissue transfer has resulted in a decrease in hospital stay and the number of overall surgeries. Importantly, due to the variability in injury pattern and complexity in reconstruction, a systematic approach toward intervention is needed to mitigate complications and optimize overall functional and aesthetic outcomes.
Keywords: facial gunshot wounds; facial reconstruction; facial trauma management